Collective morality and crime in the Americas. - Birkbeck, Christopher (Routledge studies in crime and society., 2012)
This study examines the ways in which the moral community is ""talked into being"" in relation to crime, and the objects of concern that typically occupy its attention. It maps the imagined moral universe of the virtuous and the criminal and charts the relations between these two groups in the ""history of the present."" It examines the calls to action which symbolically endow the moral community with power. And it looks at the character and content of collective moralizing. The source materials are commentaries about crime and criminal justice appearing in selected newspapers.